DESIGN OF CORPORATE CLOTHING: AESTHETIC AND ERGONOMIC ASPECTS - KULESHOVA, SVITLANA; KOSHEVKO, JULIA; KRYVYTSKA, IRYNA; ZAKHARKEVICH, OKSANA; BALABANOV, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the process of designing corporate clothing for employees and students of higher education of the Khmelnytskyi National University, which is considered as a system of "corporate style → corporate image → corporate clothing and its identity", including logos, colors, graphic elements and graphic standards of visual identification of the KhNU and their structure. Scientific novelty. The most characteristic artistic and compositional solutions and the typology of graphic elements used in the corporate style of KhNU as a means of communication for the creation of the image and brand of the higher education institution were analyzed and highlighted. Practical meaning. The developed systematization of the graphic elements of the corporate style of KhNU made it possible to generalize their artistic and compositional features and use them in the design of men’s and women’s corporate clothing for employees and students of higher education of the Khmelnytskyi National University for visual representation and broadcasting of the values and main characteristics of the educational institution. The process of creating a sketch and harmonizing the project image of corporate clothing with the help of an information model, which allows to present it as a single symbolic system with the help of modern practices of visual presentation of fashion innovations, is demonstrated. The design stages of corporate clothing samples are presented with the help of computer technologies, which provide clothing designers with wide visual and artistic opportunities in the context of modern communication practices. Artistic and design, constructive and technological solutions for men’s and women’s corporate clothing models were developed, which were produced under the conditions of the Ukrainian fashion brand ARTY Sport using a calender thermopress for sublimation. Testing of experimental samples of products took place at the exhibition dedicated to the Day of Science (Khmelnytskyi, KhNU, 2022). Research materials can be used in the development of corporate style and design of modern corporate clothing. The results of the study can be used in further scientific research on the design of other types of corporate clothing for employees and students of higher education of the Khmelnytskyi National University.